Autoimmune Hepatitis in Children: The Current State of the Problem - G. V. Volynets; A. I. Khavkin; T. A. Skvortsova; V. V. Matkash (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. To generalize the results of existing research studies carried out to investigate autoimmune hepatitis (AIH) in children, and the contemporary approaches to the diagnosis and therapy of the disease. Key points. According to the results of serological studies, two types of AIH can be distinguished in children. AIH of type 1 is diagnosed, when anti-smooth muscle autoantibodies (ASMA) and/or antinuclear autoantibodies (ANA) have been detected. AIH of type 2 AIH is diagnosed, when liver kidney microsomal autoantibodies (anti-LKM-1) and/ or anti-liver cytosolic autoantibodies (anti-LC-1) have been detected. Liver parenchymal inflammation responds well to a standard immunosuppressive therapy with prednisolone and azathioprine. Disease relapses are observed in about 40% of patients during treatment. It is expedient to treat children at least for 2–3 years before attempting to cancel the treatment, which decision should be considered only when the levels of transaminases have remained normal and IgG has been negative, or autoantibody titers have been low (1:20 using immunofluorescence method) for at least a year. Before attempting to cancel the therapy, liver biopsy and histological study should be repeated in order to exclude the possibility of residual inflammatory changes. For a small number of patients, who do not respond to standard treatment and those who suffer from frequent disease relapses, it is advisable to offer an alternative immunosuppressive treatment, the effectiveness of which is still ambiguous and poorly understood (including, in order of priority, mycophenolate mofetil, calcineurin inhibitors, rituximab, Inhibitor of tumor necrosis factor-alpha). In cases of refractoriness to therapy and the disease progression to liver cirrhosis and its decompensation, liver transplantation is justified. It is shown that AIH might relapse after liver transplantation. De novo AIH develops after liver transplantation as a result of non-autoimmune diseases; it is characterized by the presence of autoantibodies (ANA, ASMA and typical or atypical anti-LKM-1), and histologically characterized by a pattern similar to that of AIH. De novo AIH after liver transplantation responds well to a classical immunosuppressive therapy, but not to a standard antiretroviral therapy. In the review, we discuss issues associated with the clinical manifestations and diagnosis of AIH in children. Approaches to the treatment and long-term observation of such children are reviewed, including, i.e., those formulated by the main group of the European Society for Paediatric Gastroenterology Hepatology and Nutrition (ESPGHAN) members.Conclusion. Autoimmune hepatitis (AIH) in children has a progressive course with the outcome to liver cirrhosis. The presented review has summarized approaches to the diagnosis and selection of AIH therapy in children.